How do nurse academics value and engage with evidence-based practice across Australia: Findings from a grounded theory study. (June 2016) - Malik, Gulzar; McKenna, Lisa; Griffiths, Debra
Abstract: Background: Integrating evidence-based practice (EBP) into undergraduate education and preparing future nurses to embrace EBP in clinical practice becomes paramount in today's complex and evolving healthcare environment. The role that EBP plays in the practical lives of nursing students will depend on the degree to which it is promoted by academics, how it is incorporated into courses and its application to clinical setting. Hence, nursing academics play a crucial role in influencing its integration into curricula. Drawn from a larger doctoral study, this paper presents findings discussing how nurse academics value and engage with EBP. Methods: Grounded theory was employed to explore processes used by nursing academics while incorporating EBP into teaching and learning practices. Twenty-three academics across Australian universities were interviewed. Nine were also observed while teaching undergraduate students. Data were collected from semi-structured interviews and non-participant observation. In keeping with the tenets of grounded theory, data collection and analysis continued until theoretical saturation was reached. In total, four categories emerged. This paper focuses on the category conceptualised as Valuing and Engaging with EBP . Results: How nursing academics valued and engaged with EBP was closely associated with meanings they constructed around understanding it, attitudes and commitment to implementation while teaching and working clinically. Different opinions also existed in regard to what actually constituted EBP. However, they engaged with and valued EBP by keeping themselves up-to-date, being involved in research activities, using evidence in teaching, therefore leading by example. Participants identified a number of barriers influencing their engagement with EBP including heavy workloads, limited time, lack of commitment within their schools, lack of confidence with teaching EBP, and complexity of EBP application. Faculty clinical practice, committed academics, workload management and continuing education were highlighted as facilitators. Conclusion: A number of barriers prevented academics from fully engaging with EBP at academic or practice levels. Academic institutions and practice settings need to employ strategic planning to overcome such barriers. Highlights: Learning about nursing academics' understanding and engagement with EBP is timely with the need to produce evidence-based practitioners. Efforts of academic institutions are critical to ensure nurse academics are provided with opportunities to embrace EBP. Robust initiatives targeting to increase academics' engagement with EBP and aiming to overcome barriers are recommended.